Analisis Kesalahan Sintaksis, Morofologi, dan Penulisan Huruf Arab dalam Pembuatan Karangan Berbahasa Arab di Pondok Pesantren - Umma Khoirotus Soleckah; Wahyu Hanafi Putra; Kunti Nadiyah Salma (Lisanan Arabiya: Jurnal Pendidikan Bahasa Arab, 2023)
The aims of this study were: 1. To find out the forms of grammatical, morphological and spelling errors in writing papers, 2. To know the analysis of grammatical, morphological and spelling errors in writing, 3. To demonstrate how to solve problems with grammatical, morphological and spelling errors in essay writing. The research approach used is qualitative research. And data collection techniques used by researchers are observation, interviews, and documentation. The research was conducted at the Ar Risalah Modern Islamic Boarding School. The results of the study: there are three forms of errors, namely: 1) morphological errors, 2) grammatical errors, 3) spelling errors. In the analysis there were 73 errors: 14 in morphological form, and grammatical errors there were 23 errors. As for overcoming the problem of morphological and grammatical errors in writing essays, namely: 1) explaining the material again, 2) giving examples of grammar, 3) repeated exercises and practices, 4) choosing learning methods